The Effect of Intellectual Capital (VACA, VAHU, and STVA) on Firm Value in Healthcare Sector Companies on the IDX - Budhi Adhiani Christina; Andreas Riko Candra; Prima Ayundyayasti; Sarana Sarana; Mardinawati Mardinawati (Citakonsultindo, 2024)
Firm value is the accomplishment of a company as an example of public trust. Company value can differ from the value of tangible assets owned. This difference indicates the presence of hidden value, which is considered to be the company's intellectual capital. This study aims to determine the influence of Intellectual Capital (VACA, VAHU, and STVA) on firm value (PBV) in healthcare sector companies and how the influence of financial performance (ROA) moderates the relationship. Sampling is done by purposive sampling, so a sample of 16 companies with 48 observational data was obtained through documentation techniques. Data analysis was done using the panel data regression method and Moderated Regression Analysis (MRA) using the Eviews 12 application. The results showed that VACA and VAHU partially had a significant effect on firm value, while STVA partially had no significant effect on firm value. Financial performance projected by ROA can moderate the relationship between VAHU and firm value, but cannot moderate the relationship between VACA and firm value or STVA and firm value.